Recombination within the human embryonic xi-globin locus: a common xi-xi chromosome produced by gene conversion of the psi xi gene. - Hill, A; Nicholls, R; Thein, S; Higgs, D (1985)
The duplicated human embryonic alpha-like globin genes encode a 5' functional zeta (xi 2) gene and a highly homologous pseudogene (psi xi 1). We have identified chromosomes with a xi 2-xi 1 rather than a xi 2-psi xi 1 arrangement by genomic mapping and oligonucleotide analysis. The DNA sequence of a cloned downstream xi-like gene provides direct evidence for the conversion of a psi xi 1----xi 1 gene, by a xi 2 gene. We present data suggesting that this gene conversion, which removed the only identifiable inactivating mutation in the psi xi 1 gene, was an interchromosomal event. The xi 2-xi 1 arrangement is common in all eight populations studied representing a previously undescribed type of polymorphism between individuals. Stable mRNA transcripts from the converted gene are absent at 16-20 weeks of gestation when transcripts from the xi 2 gene are readily detectable.